Determinant Good Corporate Governance Dan Konsekuensinya Terhadap Kebijakan Dividen - Hotimah, Nunu Nurul; Hindasah, Lela (Jurnal Manajemen Bisnis, 2017)
This research is aimed at analyze the influence of Profitability, Leverage and Growth toward Dividend Payout Ratio, by considering the Corporate Governance as an interveningvariable on Non Financial Companies In Indonesia Stock Exchange 2008- 2014. Subjects in this study were the companies ranked in the Corporate Governance PerceptionIndex ranking (CGPI) conducted by the Indonesian Institute for Corporate Governance (IICG) in 2008-2014 which published their financial statements as of December 31. The samples were 40 samples selected using purposive sampling method. The data analysis technique used is classic assumption test, multiple regression and path analysis with the help of SPSS 1 for windows.Based on the results of the analysis show that the profitabilitas (ROA) positive and significant effect on dividend payout ratio, Leverage (DER) but no significant negative effect on dividend payout ratio, growth (TAG) negative and significant effect on dividend payout ratio, profitabilitas (ROA) positive and significant effect on good corporate governance, leverage (DER), positive and significant effect on good corporate governance, growth (TAG) positive and significant effect on good corporate governance, and good corporate governance (CGPI) posi tive and significant effect on dividend payout ratio.